Analisis Risiko Bencana Banjir Dan Strategi Mitigasi Berbasis Infrastruktur Drainase Berkelanjutan Di Kawasan Perkotaan Padat Penduduk - Wahyuni (CV. SINAR HOWUHOWU, 2025)
Urban flooding has become a chronic problem in densely populated areas, triggered by a combination of high rainfall intensity, rapid urbanization, and the limited capacity of conventional drainage infrastructure. This study aims to analyze urban flood risk and formulate effective mitigation strategies through a sustainable drainage approach. The research employed a mixed-methods approach, combining qualitative and quantitative data from secondary sources, field observations, interviews, and questionnaires. Spatial analysis using Geographic Information Systems (GIS) revealed that the highest flood risk is concentrated in areas with high population density and degraded drainage systems. The findings indicate that conventional mitigation strategies are not entirely effective. In contrast, the implementation of sustainable drainage infrastructure, such as biopori infiltration holes and retention ponds, was shown to significantly reduce surface runoff and increase water infiltration capacity. However, institutional and social challenges remain major obstacles to their implementation. Therefore, this study recommends an integrated mitigation framework that includes accurate risk analysis, the implementation of sustainable technology, and the strengthening of community participation.